Patterns of technology transfer in Chinese hotspots of innovative development: The perspective of the recipient firms - Henning Kroll; Esther Schricke (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
In summary, our study has highlighted that technology transfer systems in China may involve more channels, involve more partners, and in global terms be more dynamic than commonly assumed - at least in the case of well-developed urban innovation systems such as Beijing. With certainty, the times where spin-offs had to be set up for a lack of other options are over. Instead, our survey documents a vibrant set of interactions between not only science and industry but also up and down the value chain within industry itself. In terms of quantities, at least, this system does no longer appear inferior or very differently structured than those of technologically more advanced nations. Moreover, most of the surveyed companies could not find fault with many of the commonly assumed obstructions of knowledge exchange in China - such as lack of trust or unfavourable and poorly implemented regulations.
urn:nbn:de:0011-n-2281404
Keywords: 330